Resting-State Functional Connectivity in Late-Life Depression: Higher Global Connectivity and More Long Distance Connections - Bohr, Iwo J.; Kenny, Eva; Blamire, Andrew; O'Brien, John T.; Thomas, Alan; Richardson, Jonathan; Kaiser, Marcus (Frontiers in Psychiatry, 2013)
Functional magnetic resonance imaging (fMRI) recordings in the resting-state (RS) from the human brain are characterized by spontaneous low-frequency fluctuations (SLFs) in the blood oxygenation level dependent (BOLD) signal that reveal functional connectivity (FC) via their spatial synchronicity. This RS study applied network analysis to compare FC between late-life depression (LLD) patients and control subjects. Raw cross-correlation matrices (CM) for LLD were characterized by higher functional connectivity. We analysed aggregate topology metrics of networks composed of 110 brain regions and also investigated properties of connectivity in the basal ganglia. Topological network measures showed no significant differences between groups. The composition of top hubs was similar between LLD and control subjects, however in the LLD group posterior medial parietal regions were more highly connected compared to controls. In LLD, a number of brain regions showed connections with more distant neighbours leading to an increase of the average Euclidean distance between connected regions compared to controls. In addition, right caudate nucleus connectivity was more diffuse in LLD. In this study, LLD was associated with overall functional connectivity strength and changes in the average distance between connected nodes, but did not lead to global changes in small-world or modular organization.